Cotinine Testing as a Component of Screening for Tobacco use Cotinine Testing as a Component of Screening for Tobacco use in a Pediatric Hospital - Kelsey K. Schmuhl; Alexander S. Golec; Andrea E. Bonny; Brittny E. Manos; Ashley L. Merianos; Samuel W. Stull; Ashley M. Ebersole (Health Behavior Research)
The aim of this retrospective cohort study was to assess documented nicotine use history, withdrawal, and intervention with nicotine replacement therapy (NRT) for patients admitted to a quaternary children’s hospital who tested positive for cotinine. Patients tested positive for cotinine during 26 of 220 (12%) admissions in which cotinine testing was done. The electronic medical records (EMRs) of these 26 admissions (25 eligible patients; one patient admitted twice) were reviewed for documentation of tobacco product use history, cotinine urine test results, nicotine- related withdrawal symptoms, and prescription of NRT. Data were analyzed using descriptive statistics. Most patients were admitted for overdose or intentional ingestion. 25 of 26 (96%) had tobacco use history documented, and eight (32%) had incongruent documentation. Two patients (50%) with documented nicotine withdrawal were prescribed NRT. This study illustrates missed opportunities to engage patients in addressing tobacco use.